Clustering technique for analysing environmental attitude among undergraduate students in Purulia district, West Bengal - Subir Sen; Surajit Mahato; Ramesh Chandra Mahato; Bishal Das (Universitas Negeri Yogyakarta, 2025)
This study aims to explore inter-dimension relationships in the environment, identifying clusters based on independent variables (Stream, gender, location) and their consequences on Environmental Behaviour (EB), Environmental Opinion (EO), and Environmental Emotion (EE) among undergraduates in Purulia district, West Bengal. Using a descriptive survey method with randomly sampled participants, the study employs the